2022
DOI: 10.1001/jamanetworkopen.2022.37960
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Health Coaching Intervention for Patient-Family Dyads to Improve Outcomes Among Adults With Diabetes

Abstract: ImportanceMore than 75% of US adults with diabetes do not meet treatment goals. More effective support from family and friends (“supporters”) may improve diabetes management and outcomes.ObjectiveTo determine if the Caring Others Increasing Engagement in Patient Aligned Care Teams (CO-IMPACT) intervention improves patient activation, diabetes management, and outcomes compared with standard care.Design, Setting, and ParticipantsThis randomized clinical trial was conducted from November 2016 to August 2019 among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Eighteen RCTs investigated the effects of family diabetes management interventions, employing various approaches and theories. Among these, eight studies were carried out in developed countries: Ireland (Keogh et al, 2011), United States (McEwen et al, 2017; Nelson et al, 2017; Rosal et al, 2011; Rosland et al, 2022; Trief et al, 2016), Republic of China-Taiwan (Kang et al, 2010) and Spain (Coria et al, 2020). Additionally, ten RCTs were implemented in developing countries: Chile (García-Huidobro et al, 2011), Iran (Maslakpak et al, 2017; Tabasi et al, 2014), Brazil (Gomes et al, 2017), Thailand (Poonprapai et al, 2022; Sukchaisong et al, 2022; Wichit et al, 2017; Withidpanyawong et al, 2019), Marshall (McElfish et al, 2019), and Indonesia (Subrata et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen RCTs investigated the effects of family diabetes management interventions, employing various approaches and theories. Among these, eight studies were carried out in developed countries: Ireland (Keogh et al, 2011), United States (McEwen et al, 2017; Nelson et al, 2017; Rosal et al, 2011; Rosland et al, 2022; Trief et al, 2016), Republic of China-Taiwan (Kang et al, 2010) and Spain (Coria et al, 2020). Additionally, ten RCTs were implemented in developing countries: Chile (García-Huidobro et al, 2011), Iran (Maslakpak et al, 2017; Tabasi et al, 2014), Brazil (Gomes et al, 2017), Thailand (Poonprapai et al, 2022; Sukchaisong et al, 2022; Wichit et al, 2017; Withidpanyawong et al, 2019), Marshall (McElfish et al, 2019), and Indonesia (Subrata et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the baseline and post-intervention HbA1c levels were measured as the outcome measures. HbA1c values were assessed in six trials after 3 months (Keogh et al, 2011; Maslakpak et al, 2017; Subrata et al, 2020; Sukchaisong et al, 2022; Tabasi et al, 2014; Wichit et al, 2017), four studies after 6 months (García-Huidobro et al, 2011; Gomes et al, 2017; Kang et al, 2010; McEwen et al, 2017), two studies after 9 months (Poonprapai et al, 2022; Withidpanyawong et al, 2019), and six studies after 12 months (Coria et al, 2020; McElfish et al, 2019; Nelson et al, 2017; Rosal et al, 2011; Rosland et al, 2022; Trief et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FAMS’ null mean effects on HbA1c are consistent with the broader literature on family-focused interventions. In a recent trial evaluating another family-focused intervention among adults with type 2 diabetes, Rosland et al [22] also found improved self-efficacy and self-care behaviors, but not HbA1c. In Zhang et al’s 2021 meta-analysis of family-based interventions for adults with diabetes, there was an overall effect on HbA1c, but the effect was much larger when the length of follow-up was 6 months or less [45].…”
Section: Discussionmentioning
confidence: 99%
“…There is also limited understanding of factors that might explain effects of family-focused interventions on HbA1c [17 20 21]. Although past studies have shown that family-focused interventions lead to improvements in self-efficacy and self-care [15 22], it is not clear whether these factors drive improvements in HbA1c. Furthermore, it remains unclear if improvements in family/friend involvement drive improvements in HbA1c.…”
Section: Introductionmentioning
confidence: 99%